Digital Literacy Questionnaire Instrument: Based on the Integration of Elementary School Students' Characteristics - Afandi, 'Alia Nur Husna; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra; Pristiani, Riska (Universitas Pendidikan Ganesha, 2024)
In this era of technological progress, adequate digital literacy skills are needed for elementary school students. The problem that arises is the lack of measuring tools to capture digital literacy skills specifically for elementary school students. Where this measuring instrument can be used as a tool to profile elementary school students' digital literacy abilities. The results of the digital literacy skill profile portrait can be used by teachers to carry out future intervention strategies. Based on this, this research aims to create a questionnaire instrument that can measure digital literacy skills in elementary school students. This research uses seven areas of digital literacy that have been determined by UNESCO (2018). Aspects of the characteristics of elementary school students including cognitive, language, motoric, social-emotional are also taken into consideration. This research applies a 4D model. Data was collected using a validity questionnaire instrument. The test subjects were elementary school teacher education lecturers who had a track record of research related to educational technology. Data were analysis using descriptive analysis techniques to describe the validity of the products that had been developed. The validation results show that the indicators for developing this instrument have been prepared based on the digital literacy theory promoted by UNESCO in 2018, and have also been detailed with the characteristics of elementary school students. According to experts, this instrument can be considered an excellent category and is ready to be used in measuring the digital literacy skills of elementary school students.